Democratic Republic of the Congo : Technical Assistance Report-Governance and Anti-Corruption Assessment. (IMF Staff Country Reports; Country Report, 2021)
At the request of His Excellency the President of the Republic and Head of State, the Legal (LEG) and Fiscal Affairs (FAD) Departments of the IMF conducted an assessment of governance and corruption mission in Kinshasa, Democratic Republic of the Congo (DRC) from December 9 to 20, 2019 (the 'mission').1 The objectives of the mission were to discuss with the authorities (i) a diagnostic of governance issues in the DRC; and (ii) to articulate measures to help improve governance and the fight against corruption.